Ten years of technological change in dry zone agriculture - Naing, Zaw Min (Michigan State University, 2017)
This report outlines recent (2007-2017) changes in agricultural practices for the main field crops grown in Myanmar’s Dry Zone, based on information gathered from the Rural Economy and Agriculture Dry Zone (READZ) survey. Myanmar’s Dry Zone is a vast area in the North-Central part of the country, spanning three different regions (Sagaing, Mandalay and Magway) and including the country’s second-largest city of Mandalay. The survey was carried out in April of 2017 in the townships of Budalin, Myittha, Magway and Pwintbyu. One objective of the survey was to assess trends in production patterns and practices for four of the major field crops grown in the area: rice, groundnut, sesame, and green gram. This was done by collecting recall data for three time periods: the year of the survey (2017, corresponding to the 2016-2017 growing season), five years prior (2012), and ten years prior (2007). Each farmer was asked only about their most important crop, so the results pertain not to all farmers growing a given crop, but rather to those specializing in each crop. This analysis allowed us to compare how production of the four major crops has evolved over the past ten years in terms of seasonality, technology and input use, and yields, and to identify evidence of any technological change and modernization occurring.